Gastroprotective activity of the hydroethanolic extract and ethyl acetate fraction from Kalanchoe pinnata (Lam.) Pers. - Flávia Sobreira; Leandro Santoro Hernandes; Alberto Vetore-Neto; Ingrit E. Collantes Díaz; Fernanda Carvalho de Santana; Jorge Mancini-Filho; Elfriede Marianne Bacchi (Universidade de São Paulo, 2017)
ABSTRACT Peptic ulcers are an important pathology, and the search for safer and more effective treatment methods is of paramount importance. In this study, we assess the gastroprotective effects of the hydroethanolic extract (HE) and ethyl acetate fraction (EAF) from Kalanchoe pinnata leaves against an ethanol/HCl-induced ulcer model in rats. The HE reduced gastric lesions by approximately 47% (400 mg/kg). A significant inhibition of the gastric lesions by 50% was observed after pretreatment with the EAF (200 mg/kg). Quercetrin and quercetin 3-O-α-L-arabinopyranosyl-(1→2)-α-L-rhamnopyranoside were isolated and identified in the flavonoid fraction (EAF) by HPLC and NMR analyses because this fraction showed the highest gastroprotective effect. This fraction demonstrated high antioxidant activities (CE50=41.91 µg/mL) by DPPH in comparison with Trolox(r) and 11.33 mmol Trolox(r) equivalent by ORAC. In conclusion, the HE and FAE from K. pinnata displayed gastroprotective activity in rats, most likely due to the presence of flavonoids.